Anterior Cruciate Ligament Reconstruction Using Bone-Patellar Tendon-Bone Allograft in Patients Aged 50 and Older Leads to Improved Activity Levels and Acceptable Patient-Reported Outcomes - Stephen M. Sylvia, M.D; Thomas J. Gill, M.D; Ian D. Engler, M.D; Kaitlin M. Carroll, B.S; Matthew J. Salzler, M.D (Elsevier, 2021)
Purpose: To evaluate patient-reported outcomes in patients aged 50 years and older undergoing anterior cruciate ligament reconstruction (ACLR) using bone-patellar tendon-bone (BPTB) allograft with minimum 2-year follow-up. Methods: A retrospective review was performed on a consecutive series of patients aged 50 and older who underwent ACLR using BPTB allograft by a single surgeon with minimum 2-year follow-up. Postoperative International Knee Documentation Committee (IKDC), Lysholm, and Physical Component Summary of the 12-item Short-Form Health Survey were used to assess outcomes, as well as preoperative and postoperative Tegner activity scores, which were compared using a paired sample t test. Results: Fifty patients met inclusion criteria, with a mean age of 55.3 ± 4.4 years and mean follow-up of 4.8 ± 1.9 years. Tegner activity scores improved from a mean preoperative score of 3.26 to a mean postoperative score of 5.25 (P < .001). The mean postoperative scores for Lysholm, IKDC, and Physical Component Summary were 87.3, 81.1, and 54.3, respectively. In total, 36 (72%) patients achieved a patient acceptable symptom state score for IKDC and 37 (74%) patients achieved a minimal clinically important difference for Tegner activity score. Thirty-eight (76%) patients reported good-to-excellent results, 6 (12%) patients reported fair results, and 6 (12%) patients reported poor results. Conclusions: ACLR with BPTB allograft in patients aged 50 and older leads to good patient-reported outcomes with significantly increased postoperative activity status at a minimum 2-year follow-up. Level of Evidence: Level IV, therapeutic case series.